1966
DOI: 10.1139/m66-003
|View full text |Cite
|
Sign up to set email alerts
|

The Induction by Lysozyme of an L-Type Growth in Mycobacterium Tuberculosis

Abstract: Lysozyme in combination with ethylenediamine tetraacetic acid (EDTA) gives rise to spheroplasts when Mycobacterium tuberculosis is cultured in a nutritionally complete Tween 80 – albumin medium. These spheroplasts do not multiply in this medium, but when such forms, stabilized by the presence of sucrose and Mg++, are inoculated into PPLO agar or broth an L-form of growth is initiated. A CO2requirement was demonstrated by L-forms grown on solid media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The accumulation ofenough host macromolecules about the surface of Phe I should render it somewhat indistinguishable from the host's self Most Phe I appear to have an intact cell wall. This is interesting in light of the fact that Willet and Thacore found that either acid phosphatase or phospholipase C could render H37Ra susceptible to lysozyme, with subsequent protoplast formation (1263) and, with high enough numbers of bacteria, even L-form development (1262). The addition of lysozyme to cell cultures of J-111 human monocytes has made possible the formation of protoplasts in these host cells (1147).…”
Section: Arabinogalactan and Arabinogalactan-mycolatementioning
confidence: 99%
“…The accumulation ofenough host macromolecules about the surface of Phe I should render it somewhat indistinguishable from the host's self Most Phe I appear to have an intact cell wall. This is interesting in light of the fact that Willet and Thacore found that either acid phosphatase or phospholipase C could render H37Ra susceptible to lysozyme, with subsequent protoplast formation (1263) and, with high enough numbers of bacteria, even L-form development (1262). The addition of lysozyme to cell cultures of J-111 human monocytes has made possible the formation of protoplasts in these host cells (1147).…”
Section: Arabinogalactan and Arabinogalactan-mycolatementioning
confidence: 99%
“…Ferrous ammonium sulfate and sodium citrate provide iron and citrate in solution. The requirement for MgSO4 in defined media has been recognized for many years; its presence may be significant for cell wall synthesis and membrane stabilization (13).…”
mentioning
confidence: 99%
“…The most likely mechanism of CWDforms formation seems to be the lytic activity of lysozyme within phagolysozomes after phagocytosis of mycobacteria by macrophages (Willett and Thacore, 1966;Gerasimov et al, 2003).…”
Section: Formation Of Cwd-forms Of Mycobacteria In Vivomentioning
confidence: 99%